Analysis of Code Mixing on the Youtube Channels of Viral Z-Generation Indonesian Youtubers - Arline Camelia Najuar; Wulan Rahmatunisa; Marwito Wihadi (English Lecturers and Teachers Association (ELTA), 2025)
This study aimed to identify the types and functions of code mixing found in Shasa Zania and Kiara Leswara on their YouTube channels. The methodology that is used in this study is a qualitative research method, and the research design is the case study. The result of this study showed that there are 3 types of code mixing namely insertion, alternation, and congruent lexicalization. Starting from Insertion 56,25%, alternation 26,04%, and finally congruent lexicalization 17,71% the total is 100%. Moreover, the research also showed that 5 functions of code mixing were found in the videos such as talking about a particular topic, the intention of clarifying the speech content for the interlocutor, interjection, being empathetic about something, and repetition used for clarification. Starting from talking about a particular topic 34,5%, the intention of clarifying the speech content for the interlocutor 29,6%, interjection 17.3%, being empathetic about something 9.9%, repetition used for clarification 8.7%. Keywords : Sociolinguistics: Code Mixing, Youtube